Dance Literacy As An Expression of Experience and Creativity in Dance Education - Nurharini, Atip; Ratnaningrum, Ika; Yanuarita Sutikno, Putri; Ahmadi, Farid; Permata Hapsari, Intan (International Journal of Psychosocial Rehabilitation, 2019)
This article elaborates on reading and writing the body movement as an expression that can be depicted through dance creativity. In reading the move as an expression of communication, students can find ideas, thoughts, minds, or feelings which are eventually expressed through dance moves. Activities in dance literacy help students develop their dance reading skills of what they see related to the choreography. Moreover, the dance created through dance literacy learning is students’ skills in using body movement language, including observation, implementation, exploration, construction, and creativity. The effect of dance literacy in dance education at school is as a medium to implement habit formation to the students about dance literacy; therefore, it can foster activities such as the expression of feeling, sensitivity, dance experience, and creativity, which are eventually arranged as a dance creation.